The behavioural trend of ghosting in the professional context – a scoping review on the empirical mapping of ghosting in vocational surroundings - Laureana Teichert (Cogent Business & Management)
This scoping review elucidates the behavioural trend of ghosting in vocational surroundings. Ghosting originates from private contexts, specifically from the dating sector. Due to power shifts within labour markets, the phenomenon entered vocational surroundings, impeding organisations’ daily operations and recruiting processes. Ghosting describes the behaviour of one party abruptly terminating contact with another party, without providing explanatory information or indications. Disappearing like ‘a ghost’ leaves ghosted parties uncertain about the situation. The current state of research on ghosting in vocational surroundings is sparse, mainly focusing on the candidate perspective to generate insights and enhance understanding. By conducting a qualitative content analysis, this scoping review examines the scope of preceding research, generating a scoping map to demonstrate the coverage of current knowledge on the respective research field, as well as outlining overlaps and gaps. Previous research differs substantially in the scope, with each study covering a different area of ghosting in vocational surroundings. The main overlaps are to be found on the perspective of the candidate side, but working towards various research objectives. The state of research to date is sparse and challenging to compare across studies, therefore examined broader by each research focusing on a different scope.